Insights into the diverse roles of the terminal oxidases in Burkholderia cenocepacia H111 - Sarah Paszti; Olivier Biner; Yilei Liu; Kim Bolli; Sarah Dorothy Jeggli; Gabriella Pessi; Leo Eberl (Scientific Reports)
Abstract Burkholderia cenocepacia H111 is an obligate aerobic bacterium which has been isolated from a cystic fibrosis (CF) patient. In CF lungs the environment is considered micro-oxic or even oxygen-depleted due to bacterial activities and limited oxygen diffusion in the mucus layer. To adapt to low oxygen concentrations, bacteria possess multiple terminal oxidases. In this study, we identified six terminal oxidases of B. cenocepacia H111 and constructed reporter strains to monitor their expression in different environments. While the heme-copper oxidase aa 3 (cta) was constitutively expressed, the bd-1 oxidase (cyd) was induced under oxygen-limited growth conditions. The cyanide-insensitive bd-type terminal oxidase (cio-1) was mainly expressed in cells grown on the surface of solid medium or in liquid cultures in presence of cyanide, which is known to be produced in the CF lung by the often co-residing CF pathogen Pseudomonas aeruginosa. Indeed, a cio-1 insertional mutant was not able to grow in the presence of cyanide confirming the important role of Cio-1 in cyanide resistance. The caa 3 oxidase (caa), was only expressed under nutrient limitation when cells were grown on the surface of solid medium. We also investigated the involvement of two regulatory systems, Anr and RoxS/RoxR, in the expression of cio-1 and cyd. Our data suggest, that, given that Cio-1 is only present in prokaryotes and plays an important role in the defense against cyanide-producing P. aeruginosa, it may be a valuable drug target for treatment of polymicrobial infections in CF patients.